Immune response induced by fermented milk with potential probiotic strains isolated from artisanal Cocido cheese - Lourdes Santiago-López (Taylor & Francis Group, 2018)
Fifteen strains of lactic acid bacteria isolated from artisanal Cocido Mexican cheese were evaluated for their probiotic potential and capacity to modulate the immune system. The results revealed that the strains J20, J23, J24, J25, J27, J28, J32 and J37 presented the highest potential probiotic. Some strains showed resistance to antibiotics; however, they did not exhibit haemolytic activity or mucin degradation. The auto-aggregation capacity ranged from 9.54% to 47.80%, and the hydrophobicity was 21.1%, 63.4% and 78.8% for J27, J24 and J37, respectively. The strains showed high survival capacity (>80%) under different storage conditions and the β-galactosidase activity was 241.77–249.25 MU. Furthermore, the administration of fermented milk by specific strains of Lactobacillus enhanced IL-10 levels and upregulated IL-6 and IgA levels in serum samples of rats. Therefore, the evaluated strains may modulate the immune system and may be good candidates for their inclusion in the manufacture of probiotic-fermented milk.